Differentiate Learning Management to Optimize Student Needs and Learning Outcomes in An Independent Curriculum - Mukhibat, Mukhibat (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to manage teacher performance in junior high schools by applying a differentiation learning model to optimize students' needs and learning outcomes. The method used in this study is the experimental method, namely by testing the differentiation learning model in students when learning whether it is following the needs of students, then presenting student learning outcomes based on the differentiation model in the independent curriculum. The experimental method aims to improve students' thinking skills in discovering and understanding a concept or theory of the subject being studied. The results showed that the application of the differentiation model to learning Indonesian could improve student learning outcomes and the learning model to be differentiated according to the needs of students, especially in the current implementation of the independent curriculum, which can be seen from the main pattern of meeting 1 with a classification that is quite decent to admirable in the second meeting pattern 2. This study concludes that the differentiation model can be used during learning because it suits the needs of students and can improve student learning outcomes.